Perceptions of Health Workers on the Implementation of Polio Immunization in Manokwari District, Indonesia - Marisan, Hendrik; Windiyaningsih, Cicilia; Sunita, Anna (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Polio immunization remains a crucial strategy for polio eradication in Indonesia. Understanding health workers’ perspectives is important for strengthening program implementation and ensuring optimal community participation. Method: This qualitative study was conducted in Manokwari District in 2024. Data were collected through in-depth interviews with 15 health workers selected purposively. The interviews explored perceptions, challenges, and strategies related to the polio immunization program. Data were analyzed thematically. Result: The analysis revealed two overarching themes. The first was health innovation, encompassing knowledge, perceived susceptibility and severity, observability, and complexity of the immunization program. Health workers emphasized the importance of clear information and simple procedures to increase acceptance. The second theme was social communication strategies, highlighting the crucial role of interpersonal communication, health worker commitment, and family support in motivating communities to participate. Barriers such as misinformation and limited resources were also identified. Conclusion: Health workers’ perceptions underline the significance of innovation and communication in enhancing community involvement in polio immunization. Strengthening health workers’ communication capacity and engaging family support are recommended to improve program effectiveness.